Advances in Understanding Local Tsunami Hazards in Southern California: A Review - Mark Legg (Science of Tsunami Hazards, 2025)
Local tsunami hazards in Southern California have been understated in the past due to the region's dominant strike-slip faulting. Recent large-scale Pacific-wide tsunamis and local events have renewed focus in the region. Southern California's complex tectonic setting, a result of the transition from subduction to transform faulting, creates numerous active faults capable of vertical seafloor displacement. Historical records, though sparse, indicate past local tsunami occurrences, supported by paleotsunami deposits. The primary sources for local tsunamis are identified as tectonic fault rupture and large submarine landslides. Significant advances in understanding these hazards stem from improved regional tectonic models, high-resolution seafloor mapping, detailed source characterization, enhanced earthquake monitoring, and expanded tsunami gauge networks. Future research should prioritize identifying geological evidence of past events and developing more accurate dynamic models for complex fault systems to refine hazard assessments and inform disaster preparedness.